Journal of the Royal Statistical Society. Series A. Statistics in society - De Stavola, Bianca L.; Kuha, J.; Royal Statistical Society (Great Britain) (Oxford University Press, 2023)
'Series A' publishes papers that demonstrate how statistical thinking, design and analyses play a vital role in life and benefit society.
Keywords: Statistics : Periodicals